(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
This study was conducted to detect the bioactive compounds in hot aqueous Turmeric (Curcuma longa) roots extract and study its effectiveness in inhibiting a number of gram-negative and positive bacteria and two types of molds. It was found that the turmeric extract contains a number of active compounds, the most important of which are flavonoids and resins, in addition to volatile oils, while it does not contain The extract contains alkaloids, glycosides, saponins, steroids, tannins, terpenes, and coumarins, and the total amount of phenolic substances in the extract amounted to 7.20 mg g-1 of gallic acid, and the percentage of curcumin in the extract amounted to 8.49 mg g-1. Turmeric root extract did not show high inhibitory activity at all concentrations against gram-negative bacteria, especially Escherichia coli and Klebsiella pneumonia bacteria. On the contrary, gram-positive bacteria had weak resistance to the extract, specifically at concentrations of 150 and 200 mg g-1, as they reached diameters of Staphylococcus aureus bacteria 14.00 and 14.50 mm at concentrations of 150 and 200 mg ml-1, respectively, and Bacillus subtilis bacteria 22.50 and 24.50 mm at concentrations of 150 and 200 mg/ml, respectively. The results showed that there were significant differences in the percentage of mold inhibition, and the highest percentage of inhibition reached 85.24 for the turmeric root extract at a concentration of 200 mg ml-1 for Alternaria alternata mold, and the lowest percentage of inhibition reached 28.57% at a concentration of 50 mg ml-1for Aspergillus niger.